Czynniki i poziomy analizy w badaniach konsumpcji żywności - Sojkin, Bogdan (Wydział Prawa i Administracji UAM, 1994)
The paper outlines basic types of investigation of the determinants of food consumption. Particular attention has been drawn to the necessity of carrying out the analysis of food consumption on different levels: micro, mezo and macro. This approach enables us to differentiate between different levels of the influence of individual determinants depending on the assumed level of analysis.
Factors and levels of analysis in the research into food consumption